Specific Performance in the Civil Law: Mediating Between Inconsistent Principles Inherited from a Roman-Canonical Tradition via the French Astreinte and the Québec Injunction - Vlavianos, George (Revue générale de droit, 1993)
Traditionally, inexecution of a contractual obligation in the civil law gives rise to an award in damages. This principle stems from Roman law of the classical period, which held to the maxim Nemo praecise cogi potest ad factum. In the post-classical period, however, the influence of ecclesiastical courts and the Christian notion of fidei laesio imposed itself on the classical pre-eminence of damages. Consequently, contractual obligations were often specifically enforced by secular courts based on the pacta sunt servanda doctrine of the canon law. Yet damages and specific performance, it is argued, are from the outset conceptually irreconcilable remedies. The full import of the nemo praecise principle prohibits all acts compelling the debtor to perform, whether such compulsion be physical or one of conscience. Pacta sunt servanda, on the other hand, maintains that that which has been promised should be performed, by force if necessary.In France, the mechanism of astreinte — a comminatory fine imposed on the debtor upon his failure to comply with a court order — is used to specifically enforce contractual obligations. This is done despite the fact that execution in kind is not expressly sanctioned by the Code civil.In Québec, courts have been slow to acknowledge the suitability of specific performance in the context of contractual obligations. The source of such hesitation is codally rooted, as the Civil Code of Lower Canada, in terms similar to the French Code civil, enunciates the supremacy of damages at article 1065. But this situation will change with the arrival of the new Civil Code of Québec. With this reorientation of the substantive law, Québec courts will be procedurally better equipped to enforce specific performance than their French counterparts. In essence, via the injunction, a court may physically compel a recalcitrant debtor.Despite its common law origins, the author contends that the injunction is not incompatible with the law of obligations in Québec. Any perceived incompatibility in the realm of contract law arises from the initial irreconcilability of damages and specific performance.